The ‘Minimum Dietary Diversity for Women’ (MDD-W) Indicator is related to household food insecurity and farm production diversity: Evidence from rural Mali - Adubra, Laura; Savy, Mathilde; Fortin, Sonia; Kameli, Yves; Kodjo, Niamké Ezoua; Fainke, Kamayera; Mahamadou, Tanimoune; Le Port, Agnès; Martin-Prével, Yves (Oxford University Press, 2019)
With the aim of contributing to this emerging literature, we investigated: (i) how MDD-W is linked to household food insecurity based on the Household Food Insecurity Access Scale (HFIAS) and on the Household Hunger Scale (HHS); (ii) how MDD-W is linked to farm production diversity; and (iii) whether contextual factors such as household wealth status modify these relationships. As a secondary objective, we also checked whether all of these associations held, or not, when the number of food groups consumed was used as a continuous variable, in order to conclude on the cost of dichotomization.